(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Several experiments with single pair matings have been carried out in order to estimate the reproductive parameters of a field-collected population of Ceratitis capitata Wied., after one year of continuous rearing under constant laboratory conditions. The comparative study between a 20 year-old laboratory colony and a field-collected strain (11th generation) showed that, in general, these populations did not differ significantly in larval growth and reproductive parameters. On the other hand, differences between reproductive characters of the F 1 and F2 hybrids were not found. So, it was concluded that a good adaptation process of a newly field-collected population of this species can be obtained and it is possible to get a high adult fitness after one year of rearing with our laboratory methodology. It was also considered that the composition of the larval diet and the oviposition cages were the most important requirements for this success. Polygonal, polynomial and power-exponential functions have been fitted to the experimental data in order to study the variation of the fecundity rate along the female’s life span. The last onewas the most adequate to explain this biological phenomenon, and its parameters are reported.